Renin angiotensin-aldosterone system blockers: chronic kidney disease and cardiovascular risk - Ivanov, D.D.; Kuryata, O.V.; Garmysh, I.P. (KIDNEYS, 2021)
Reducing the risk of cardiovascular events is one of the most topical issues of modern medicine. Patients with chronic kidney disease stage 3 or lower, according to international guidelines, refer to the group with high and very high cardiovascular risk. At the moment, all the existing recommendations share the view that the first-line drugs for lowering blood pressure among this group of patients are renin-angiotensin-aldosterone system blockers. When renal and cardiovascular pathologies are combined, in addition to traditional risk factors, there are non-traditional kidney risk factors too (anaemia, hyperhydration, hypercoagulation, etc.). Combined antihypertensive therapy is preferable in order to achieve more significant reduction in global cardiovascular risk and closer control of blood pressure.